Equilibrium and Kinetic Study of Removal Copper(II) from Aqueous Solution Using Chicken Eggshells: Low Cost Sorbent - Mohammad Jihad Madiabu; Joko Untung; Imas Solihat; Andi Muhammad Ichzan (Universitas Jenderal Soedirman, 2021)
The research aims to investigate feasibility eggshells as potential adsorbent to remove copper(II) ions from aqueous solution. Eggshells powder was characterized using X-ray diffraction, scanning electron microscopy, and Fourier transform infrared spectroscopy. Effect of copper(II) initial concentration, adsorbent dosage, and contact time have conducted. The optimum adsorption condition obtained when 0.7 g eggshells applied to 50 mg/L copper(II) solution for 50 minutes. The maximum percentage of copper(II) removal was exceeded more than 85%. Langmuir and Freundlich isotherm model were applied to describe the equilibrium adsorption. Copper(II) kinetics sorption process was fitted to pseudo-second order model with a rate constant equal to 0.516 g/mg.min. The results clearly exhibit that eggshells powder can be effectively used to remove copper(II) ions from aqueous solutions.